Narrativas sobre violência de gênero : análise antropológica de relatos publicados em redes sociais - Mánquez, Valeska Paulina Aguilera (2020)
In online and offline life, people can be victims of violence, and often these narratives of victims are left unsaid. This research investigates reports of violence, in Facebook groups, suffered by Latin American women. It is intended to answer the following questions: why do women victims of gender violence choose to publish a report revealing their narrative on the Facebook digital social media? What happens after the posts? The analyzes that will be shown on the digital platform “Facebook” act as an agency for the resignification of self, through the publication of narratives by women who are physically, sexually or symbolically abused. The purpose is to understand the new social and discursive practices and their impacts on the subjectivity of the women interviewed. Methodologically, multi-situated digital ethnography was used, which consisted of face-to-face and / or online interviews written by WhatsApp and Facebook. In addition, analyze the publications on Facebook and their comments. The women interviewed published or administered complaint pages on the social network. Among the results, the influence of the current feminist movement on the intentions of the narratives, as well as the production of new forms of subjectivity in the contemporary world.